Flux pile-up and plasma depletion at the high latitude dayside magnetopause during southward interplanetary magnetic field: a cluster event study - T. Moretto; D. G. Sibeck; B. Lavraud; K. J. Trattner; H. Rème; A. Balogh (Annales Geophysicae, 2005)
An event of strong flux pile-up and plasma depletion at the high latitude magnetopause tailward of the cusp has been analyzed based on observations by the suite of Cluster spacecraft. The multi-satellite analysis facilitates the separation of temporal and spatial features and provides a direct estimate for the strength of the plasma depletion layer for this event. A doubling of the magnetic field strength and a forty percent reduction of the density are found. Our analysis shows that roughly half of the total magnetic field increase occurs within 0.6 RE of the magnetopause and another quarter within a distance of 1.2 RE. In addition, the plasma depletion signatures exhibit temporal variations which we relate to magnetopause dynamics. Keywords. Magnetospheric physics (Magnetopause, Cusp and boundary layers; Magnetosheath; Solar windmagnetosphere interactions)